The politics of public sector performance : pockets of effectiveness in developing countries - Roll, Michael, 1976- (New York : Routledge, 2014)
'It is widely believed that the state in developing countries is weak, and the public sector especially is often regarded as corrupt and dysfunctional. This book provides an urgently needed corrective to such overgeneralized notions of bad governance in the developing world. It examines the variation in state capacity by looking at a particularly paradoxical phenomenon: effective public organizations in the midst of failure.While most literature is written from a focuses predominantly on state failure, corruption and other elements of bad governance, this book instead studies the phenomenon of Pockets of Effectiveness. In developing regions of the world there are public organisations and state-owned enterprises which provide public goods and services relatively effectively in a hostile environment dominated by bad governance. The authors provide the first systematic and comparative study of these exceptional organisations in five developing regions: Africa, Asia, South America, the Middle East and the Caribbean and offer a political economy model for why and how Pockets of Effectiveness emerge, how they manage to persist and what their reform potential is.This book will be of strong interest to students and scholars of political science, comparative politics, sociology, development, public administration and management'--
1. Introduction / Michael Roll -- 2. Pockets of effectiveness : review and analytical framework / Michael Roll -- 3. Pockets of effectiveness : lessons from the long twentieth century in China and Taiwan / Julia C. Strauss -- 4. An enduring pocket of effectiveness : the case of the National Development Bank of Brazil (BNDE) / Eliza J. Willis -- 5. Turning Nigeria's drug sector around : the National Agency for Food and Drug Administration and Control (NAFDAC) / Aituaje Irene Pogoson and Michael Roll -- 6. Taming the menace of human trafficking : Nigeria's National Agency for the Prohibition of Traffic in Persons and Other Related Matters (NAPTIP) / Antonia T. Simbine with Franca C. Attoh and Abubakar O. Oladeji -- 7.'Confidence in our own abilities' : Suriname's State Oil Company as a pocket of effectiveness / Wil Hout -- 8. Defying the resource curse : explaining successful state-owned enterprises in rentier states / Steffen Hertog -- 9. Comparative analysis : deciphering pockets of effectiveness / Michael Roll.
Keywords: Public administration -- Developed countries; Government business enterprises -- Developed countries; Administrative agencies -- Developing countries -- Evaluation